Mineralization proximal to the final Nuna suture in northeastern Australia - Olierook, Hugo; Affleck, R.G.; Evans, Noreen; Jourdan, Fred; Kirkland, Chris; Volante, S.; Nordsvan, A.R.; McInnes, Brent; McDonald, B.; Mayers, C.; Frew, R.A.; Rankenburg, Kai; et al. (ELSEVIER, 2021)
Mineralization along continental suture zones is facilitated through the frequent presence of pathways from fertile mantle source regions to crustal repositories. Due to their inherent rheological weakness, these suture zones are often concealed, which hinders surface-based observations. Here, we use zircon U-Pb and sericite 40Ar/39Ar dating, and whole-rock geochemical data, to investigate the crystallization and mineralization history from a sequence of granites (sensu lato), volcanic rocks and sedimentary rocks from the Au–Ag–Pb–Zn Empress Springs Project in northeast Australia, which are under >50 m of Phanerozoic cover and located near the interpreted ca. 1.6 Ga tectonic boundary between the North Australia Craton (Mount Isa Inlier) and Laurentia (Georgetown Inlier). Zircon U-Pb dating indicates that granite emplacement, volcanic eruptions and dolerite intrusions occurred between 1564 ± 6 and 1546 ± 13 Ma (2σ), corresponding to the 1560–1550 Ma Esmeralda Supersuite and the Croydon Volcanic Group exposed in the western Georgetown Inlier. U-Pb ages from detrital zircon grains in a sedimentary rock revealed a near unimodal ca. 1560 Ma population, likely sourced from the surrounding granitic and volcanic rocks. Sericite 40Ar/39Ar dating yielded disturbed spectra with evidence for incorporation of excess radiogenic Ar, but with a probable Carboniferous to Permian age, potentially dating the timing of gold mineralization. Geochemical similarities point towards an epithermal origin for the Empress Springs Project, consistent with post-orogenic mineralization at either ca. 1560–1550 Ma or 330–250 Ma. It is likely that a series of west-dipping lithospheric-scale faults below the Empress Springs Project, here termed the Empress Suture Zone, demarcate the final suture zone associated with the assembly of Nuna. Reactivation of the Empress Suture Zone ~1.3 b.y. after crystallization with potential contemporaneous gold mineralization attests to its longevity for fluid mobility.